IMF Research Bulletin, June 2012. (IMF Research Bulletin; IMF Research Bulletin ;, 2012)
The research summaries in the June 2012 issue of the IMF Research Bulletin are "Public Debt in Advanced Economies and Its Spillover Effects on Long-Term Yields" (by C. Emre Alper and Lorenzo Forni) and "Expansionary Fiscal Contractions: The Empirical Evidence" (by Rina Bhattacharya and Sanchita Mukherjee). The Q and A covers "Seven Questions about Income Inequality" (by Laura Feiveson). Also included in this issue are details on visiting scholars at the IMF, a listing of recently published IMF Working Papers and Staff Discussion Notes, as well as information on IMF Economic Review.